Indigenous knowledge on medicinal plants in Bhagawati Village Development Committee, Darchula, Nepal - Pant, SR; Panta, IR (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.79-81